(untitled) (Research, Society and Development, 2024)
Considering the growing demand for sustainable energy solutions and the need to reduce electricity costs, dependence on fossil fuels and deforestation, the aim of this article is to present a case study of the implementation performance of solar heating systems with sensible heat storage in Mozambique. This study investigates the efficiency of these systems when heat storage systems are integrated. The case study method includes the collection of empirical data through field measurements and computer simulations. The results indicate that the solar heater, when integrated with thermal storage systems, has high energy efficiency potential. The simulations show that, by storing the daily surplus energy, the solar heater can achieve up to two days of energy autonomy, thanks to the abundant solar radiation in the region and the thermal capacity of soapstone and thermal oil. However, these systems face challenges such as climate variability and high upfront costs. In addition, the study highlights that, with appropriate public policies and financial incentives, the adoption of solar heating systems can be a viable and sustainable solution for hot water supply in Mozambique. The implementation of such systems would not only contribute to the reduction of dependence on fossil fuels but also promote sustainable development in the country.